2016
DOI: 10.1002/cctc.201601053
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Partial Oxidation on Ag(1 1 1) from First Principles

Abstract: In this work, we examine the thermochemistry and kinetics of the partial oxidation of methanol to formaldehyde on silver surfaces. Periodic density functional theory calculations employing the BEEF‐vdW functional are used to identify the most stable phases of the silver surface under relevant reaction conditions and the reaction energetics are obtained on these surfaces. The calculated binding energies and transition state energies are used as input in a mean‐field microkinetic model providing the reaction kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Given the dearth of successful examples in which noble metal catalysts convert methane to useful products in the literature, such a finding may seem unexpected17 . However, this discrepancy can likely be attributed to the low oxygen coverages that exist at most relevant oxygen chemical potentials on noble metals due to their unfavorable formation energies18 . It should also be noted that a more stable radical TS does not imply the final state will include a methyl radical; even on Ag and Au, CH 3 * is approximately 0.8 eV more stable than a gas-phase radical.The near-zero slope of the surface-stabilized O-promoted metals can be explained by a bond-order conservation argument.…”
mentioning
confidence: 99%
“…Given the dearth of successful examples in which noble metal catalysts convert methane to useful products in the literature, such a finding may seem unexpected17 . However, this discrepancy can likely be attributed to the low oxygen coverages that exist at most relevant oxygen chemical potentials on noble metals due to their unfavorable formation energies18 . It should also be noted that a more stable radical TS does not imply the final state will include a methyl radical; even on Ag and Au, CH 3 * is approximately 0.8 eV more stable than a gas-phase radical.The near-zero slope of the surface-stabilized O-promoted metals can be explained by a bond-order conservation argument.…”
mentioning
confidence: 99%
“…It is instructive to consider our observations in light of previous microkinetic models and discuss how near-surface gas-phase diagnostics could improve such models in the future. In their theoretical work, Aljama et al 57 predicted that CH 3 (s) (the superscript "(s)" indicates surface-bound species), CH 2 O (s) , CH 3 O (s) , and CO (s) are the dominant carboncontaining surface species during methanol oxidation on Ag(111), with CH 3 (s) having the highest surface coverage of these species at all temperatures from 200 to 700 °C. In addition to expected desorption of CH 2 O, desorption of CH 3 is included in their model, but to our knowledge has not been previously observed, likely because it is challenging to detect free radicals, which decay quickly upon entering the gas phase, as Figure 9d shows.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…43 A recent computational study also showed that a low oxygen surface coverage (<0.2 ML, ML = monolayer) was needed for high formaldehyde selectivity in methanol oxidation. 6 These studies suggest that the precise control of the low surface coverage oxygen species on the catalyst surface is essential in the SCO of methanol.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, ethylene oxide is used to produce pharmaceuticals, detergents, and plastics, while formaldehyde is heavily consumed to make a variety of chemicals for the construction, automotive, and furniture sectors. Recent reports indicate that the global annual consumption of ethylene oxide and formaldehyde is over 35 million tons, each. ,, The annual global production of these chemicals is estimated to grow monotonically due to the increasing demand by the chemical industry. Thus, the SCO continues to be an active field of not only applied but also fundamental research. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation